Body fat composition and miR-378 expression profiling in patients with type 1 diabetes - Lissette Duarte; Diego F. García-Díaz; Francisco Pérez-Bravo (Korean Society of Pediatric Endocrinology, 2020)
Purpose Type 1 diabetes (T1D) is an autoimmune disease that involves genetic, epigenetic, and environmental factors. Change in body composition is a potential mechanism for explaining the increased incidence of T1D. Micro RNA-378 (miRNA-378) is a positive regulator of adipogenesis that has yet to be studied in such patients. This study aims to evaluate the miRNA-378 expression profile in peripheral mononuclear cells of T1D patients and controls and to determine its possible association with levels of body fat, interleukin-6 (IL-6), and tumor necrosis factor alpha (TNF-α). Methods Twenty-four T1D subjects and 20 controls under 18 years of age without autoimmune diseases were studied. miRNA-378 expression profile was determined by TaqMan probes. Body composition was determined by multifrequency bioimpedance. IL-6 and TNF-α serum levels were determined by LUMINEX. AntiGAD65, anti-IA2, and anti-ZnT8 antibodies were quantified in serum by enzyme immunoassays. Statistical significance was considered P<0.05. Results Similar body mass index and body fat (kg) were observed between the T1D and control subjects (P=0.55 and P=0.69, respectively). The miRNA-378 expression profile was significantly higher in T1D patients compared with the controls (P<0.05). Lower miRNA-378 expression in prepubertal controls was observed compared to pubertal controls, prepubertal T1D, and pubertal T1D (P<0.05). AntiGAD65, AntilA2, and AntiZnT8 were positively correlated with miRNA-378 (P=0.002, P=0.053, and P=0.007). No statistically significant correlation was observed between miRNA-378 expression and IL-6, TNF-α, or body fat. Conclusions Elevated miRNA-378 expression in T1D patients compared with controls is linked to pubertal stage but is not associated with proinflammatory status or body composition.